Caracterização da perda rápida de peso pré-competição em judocas - da Costa, T. N. F.; Artioli, G. G.; Vitoriano, J. N.; Vieira, T. C.; Castro, J. G. D. (Portuguese Journal of Sport Sciences, 2018)
The objective of this study was to characterize the prevalence, magnitude and main methods used for rapid weight loss in pre-competition judoka. The study included 47 judokas (13 girls and 34 boys), competing in any weight category and competitive level, as long as they were active in the sport. Each judoka completed a questionnaire regarding their last competitive season. Of the total of the judo practitioners, 100% already competed at the state level, 53.1% at the national level and 12.7% at the international level. It was found that 78.7% of the judokas already lost weight to compete, with the majority (46.0%) reducing between 2.0 and 4.9% of their body weight. Judokas initiated weight loss early (15.5 ± 6.4 years of age), with the highest prevalence at 12 years of age (27.0%). The most frequently used methods were to exercise more than usual, to train purposefully in warm places and to decrease fluid intake. The coach/ sensei and other judokas were the major influences on the weight loss behaviors. We concluded that the practice of pre-competition weight loss among judo practitioners is highly prevalent. Thus, it is necessary to carry out educational actions and to implement rules that prevent such practice.